FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SAYUR DAN BUAH DI RITEL ONLINE (Suatu Kasus pada Konsumen Ritel Online di Jakarta) - Ishfihana Rakasyifa; Gema Wibawa Mukti (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Developments in industrial revolution 4.0 era occurred in various sectors, including in agricultural sector. This encourages the growth of online retailers to sell farmers' crops such as vegetables and fruit. Consumers who initially shop at traditional or modern retail start shopping for vegetables and fruit at online retail. This change is influenced by changes in consumer purchasing behavior. Therefore this study aims to determine: 1) Factors that influence consumer purchasing decisions in shopping for vegetables and fruit in online retail. 2) The influence of these factors on the decision to buy vegetables and fruit in online retail. The method used in this study is a survey per consumer, respondents were taken using non-probability sampling techniques. The total sample population in this study was calculated using the Slovin formula. The results showed that. 1. Overall these factors have a significant contribution and influence, partially (separately) factors that significantly influence the psychological factors and personal factors, while social and cultural factors have no significant effect. 2. Simultaneously (together), psychological, personal, social and cultural factors can explain 54.4% of the decision to purchase vegetables and fruit in online retail.